Potentiality and Impotentiality in The Viceroys (1894) by Federico De Roberto - Sartori, Andrea (Quaderni d'Italianistica)

(untitled) (Iter Press, 2023)
This essay furnishes a critical interpretation of Federico De Roberto’s novel The Viceroys (1894) within the theoretical coordinates provided by Giorgio Agamben’s notions of “potentiality” and “impotentiality” (dynamis and adynamia, respectively, in Aristotle’s Metaphysics). The essay argues that two apparently marginal characters in the story—Chiara’s aborted fetus and Cavaliere Eugenio—embody a possibility that is open to a radical unpredictability, which is to say, to an “impotentiality” that contrasts both Benedetto Croce’s naturalistic reading of the novel and Vittorio Spinazzola’s materialist account of it. In fact, Chiara’s fetus and Eugenio are presented as metaphors of the power of imagination and literature embedded in life (in the bíos). Such a power is opposed to that of “race,” upon which critics usually flatten their interpretations of The Viceroys and, in particular, their readings of Consalvo’s concluding speech to his aunt Ferdinanda (“no, our race has not degenerated; it is the same as it ever was”).